PELATIHAN PEMBUKUAN SEDERHANA BAGI PELAKU UMKM DI KELURAHAN JATICEMPAKA KOTA BEKASI - Ria Ria; Kumba Digdowiseiso (LPPM Universitas Bina Bangsa, 2023)
This activity is motivated by the role of entrepreneurship through Micro, Small and Medium Enterprises (MSMEs), which is one of the cornerstones of the Indonesian economy besides cooperatives. To overcome unemployment, the Bekasi City Government (Pemkot) accelerates the growth of MSMEs, by providing free facilities or permits to MSME actors and coaching to MSME actors. The problems faced by MSMEs are marketing difficulties, limitations in innovation and technology, especially limitations in compiling simple bookkeeping. In this activity, training will be given to MSMEs in the Jaticempaka Village regarding business ethics, bookkeeping of financial transactions, marketing of goods and services, product packaging and labeling, and taxation (E-Filing). With simple bookkeeping training for MSMEs, it contributes to how to arrange bookkeeping between income and expenses, so that it can simplify the process of recording cash flow and performance obtained by MSMEs